2011
DOI: 10.1510/icvts.2011.271999
|View full text |Cite
|
Sign up to set email alerts
|

What size of left atrium significantly impairs the success of maze surgery for atrial fibrillation?

Abstract: A best evidence topic in cardiothoracic surgery was written according to a structured protocol. The question addressed was in adults with atrial fibrillation (AF), what preoperative size of left atrium impairs maze surgery success in terms of recurrence of AF. Altogether 422 papers were found using the reported search, of which 12 represented the best evidence to answer the clinical question. The authors, journal. date and country of publication, patient group studied, study type, relevant outcomes and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 12 publications
1
24
0
3
Order By: Relevance
“…Analysis of left atrial cryo-ablation failure risk factors found age, size of the LA, and pre-operative duration of AF to be risk factors of failure-to-restore SR in the whole set of patients; this was in accordance with other publications. 3234 …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of left atrial cryo-ablation failure risk factors found age, size of the LA, and pre-operative duration of AF to be risk factors of failure-to-restore SR in the whole set of patients; this was in accordance with other publications. 3234 …”
Section: Discussionmentioning
confidence: 99%
“…Te wyniki potwierdza również analiza bazy danych Towarzystwa Chirurgów Klatki Piersiowej (Society of Thoracic Surgeons) obejmującej 67 389 pacjentów z AF poddanych operacji na otwartym sercu, w której stwierdzono, że jednoczesne chirurgiczne leczenie AF nie wpływało na umieralność ani poważną chorobowość (skorygowany OR 1,00; 95% CI 0,83-1,20), ale częściej konieczne było wszczepienie stymulatora (skorygowany OR 1,26; 95% CI 1,07-1,49) [799]. Do wskaźników predykcyjnych nawrotu AF po operacji należą powiększenie lewego przedsionka, starszy wiek, ponad 10-letnie wywiady AF oraz AF inne niż napadowe [800][801][802][803][804]. Jeżeli chodzi o rodzaj AF, to wydaje się, że chirurgiczna PVI jest skuteczna w napadowym AF [805], natomiast zabiegi z wytworzeniem uszkodzeń w obu przedsionkach mogą być bardziej skuteczne w przypadku przetrwałego i długotrwale przetrwałego AF [797,803,806].…”
Section: Obserwacja Po Ablacji Przezcewnikowejunclassified
“…Left atrial diameter as a predictor of late AF recurrence after CM surgery was analyzed in a meta-analysis by Sunderland et al 12 A diameter > 60 mm showed a sensitivity of 100% for AF recurrence, whereas as a diameter < 48.3 mm showed a sensitivity of 100% for reversal of the sinus rhythm. In the study by Gillinov et al.…”
Section: Discussionmentioning
confidence: 99%